Hubungan Kecerdasan Spiritual (SQ) dengan Hasil Belajar Bahasa Indonesia - Lili Hasmi (Jurnal KIBASP (Kajian Bahasa, Sastra dan Pengajaran), 2019)
The purpose of this study was to describe Spiritual Question outcomes of Indonesian students in class VII SMP N 5 Kota Bukittinggi. The method used was the correlation method. The results found that there was a significant relationship between Spiritual Question and Indonesian language learning outcomes because the results of hypothesis testing proved that tcount was greater than ttable namely, 2.182> 1.708. Thus the results of this study there is a significant relationship between Spiritual Question with Indonesian language learning outcomes Keywords: Spiritual Question, Learning Achievement